Economic burden of ambulance transports for patients with heatstroke under climate change: comparison of the effects of gradual temperature increases and extreme heat events - Kazutaka Oka; Jinyu He; Yasushi Honda; Yasuaki Hijioka (Environmental Research Communications)
Although the risk of heatstroke is already severe in Japan, it is expected to increase due to climate change. Researchers have mainly focused on future increases in heatstroke morbidity and mortality to project the risk of heatstroke in Japan. However, the economic burden of heatstroke remains unclear. This study evaluated ambulance transport costs for patients with heatstroke as an economic burden. The study area was Tokyo, Japan. Two cases of ambulance transport costs were evaluated: (i) annual ambulance transport costs for patients with heatstroke and (ii) ambulance transport costs for patients with heatstroke during extreme heat events (defined as the daily maximum temperature occurring once every 50 years). We evaluated the ratio of (ii) to (i) to determine the impacts of extreme heat events. Five climate models associated with three greenhouse gas emission scenarios were used for future projections. Future demographic changes were also considered, with the population of ≥ the 65-year age group projected to increase due to Japan’s aging society. In contrast, the population for the 7–17 and 18–64-year age groups was projected to remain the same or decrease. The projection periods were set to the present (1985–2014), mid-21st century (2021–2050), and late 21st century (2071–2100). Present annual ambulance transport costs were estimated to be JPY 145 million. In contrast, those in the mid-and late 21st century were estimated to range from JPY 280–520 million, except under SSP5-RCP8.5 in the late 21st century, for which a significant increase was projected. Furthermore, one of the climate scenarios for the mid-21st century yielded a ratio of (ii) to (i) of ∼100%, indicating that a single extreme heat event could substantially increase the annual ambulance transport costs. These results suggest that efforts to reduce the unnecessary use of ambulances are essential to limit the future economic burden.